Psikologi Pendidikan Dan Strategi Membentuk Kepribadian Islami Perspektif Al-Qur’an - Abdul Malik; Fitrah Sugiarto (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2021)
Nowadays, the issue of national personality that is fading away and far from being noble is echoing again, this is triggered by various incidents in Indonesian society. Personality seems to be experiencing complex and complicated problems. So the contribution of Islamic Education which is a field of science that studies humans with various aspects is required to be present in this realm. Why is that because Islam is the religion of Allah which was revealed to the Apostles as Allah's guidance and grace for mankind, which guarantees the welfare of his material and spiritual, worldly and spiritual life. Islamic education is in trouble. The acceptance of the dichotonomic principle between the religious sciences and the general sciences is an indication of the fragility of the philosophical basis of Islamic education. This dichotonomy is clearly seen in the dualism of the education system in Muslim countries, including Indonesia. In fact, Islamic education wants education to be able to stimulate humans to think independently in order to face a good and happy life. This is the essential meaning of the prophet Muhammad SAW's prophetic mission, namely to educate humans, lead to the path of Allah SWT, and teach to uphold a healthy, prosperous, material, spiritual, just, and harmonious society. Prophet Muhammad SAW was sent to develop the quality of human life, purify morals and equip him with the provisions needed to face life in this world and the hereafter. The greatest mission of the Prophet Muhammad SAW was to perfect human morals, which basically means that humans have a healthy soul and personality, Al-Qur'an mentions the Prophet Muhammad SAW as the best example in this regard. So to achieve this direction requires a good and simultaneous strategy